Faithful Interpretation - Philip P. Frickey (Washington University Law Quarterly, 1995)
To me, a broader concern seemed to surround this dialogue: that of fidelity to the mission of interpretation. If "interpretation" is defined in a strictly empirical and verifiable sense, what the legal system does with the language of positive law hardly qualifies. The division between "is" and "ought" is, of course, a familiar one in the legal community itself. Every traditional theory of statutory interpretation wants to have it both ways: some "objective" limits, usually tied to "the text" or to "established canons," that promote predictability and inhibit interpretive willfulness, and some "normative" qualifications that promote justice and fairness.
Keywords: Law – Interpretation & amp; construction